Assessment of cytotoxicity and AhR-mediated toxicity in tropical fresh water sediments under the influence of an oil refinery - Suares-Rocha, Paula [UNESP]; Braunbeck, Thomas; Angelis, Dejanira de Francheschi de [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Springer, 2015)
Oil refinery effluents contain many chemicals at variable concentrations. Therefore, it is difficult to predict potential effects on the environment. The Atibaia River (SP, Brazil), which serves as a source of water supply for many municipalities, receives the effluents of one of the biggest oil refinery of this country. The aim of this study was to identify the (eco)toxicity of fresh water sediments under the influence of this oil refinery through neutral red (cytotoxicity) and ethoxyresorufin-O-deethylase (EROD) assays (AhR-mediated toxicity) in RTL-W1 cells (derived from fish liver). Once the refinery captures the waters of Jaguarí River for the development of its activities and discharges its effluents after treatment into the Atibaia River, which then flows into Piracicaba River, sediments from both river systems were also investigated. The samples showed a high cytotoxic potential, even when compared to well-known pollution sites. However, the cytotoxicity of samples collected downstream the effluent was not higher than that of sediments collected upstream, which suggested that the refinery discharges are not the main source of pollution in those areas. No EROD activity could be recorded, which could be confirmed by chemical analyses of polycyclic aromatic hydrocarbons (PAHs) that revealed a high concentration of phenanthrene, anthracene, fluoranthene, and pyrene, which are not EROD inducers in RTL-W1 cells. In contrast, high concentrations of PAHs were found upstream the refinery effluent, corroborating cytotoxicity results from the neutral red assay. A decrease of PAHs was recorded from upstream to downstream the refinery effluent, probably due to dilution of compounds following water discharges. On the other hand, these discharges apparently contribute specifically to the amount of anthracene in the river, since an increase of anthracene concentrations could be recorded downstream the effluent. Since the extrapolation of results from acute toxicity to specific toxic effects with different modes of action is a complex task, complementary bioassays covering additional specific effects should be applied in future studies for better understanding of the overall ecotoxicity of those environments.
Keywords: Neutral red assay; EROD assay; RTL-W1 cells; PAHs; Cytotoxicity; AhR